Long-term sulfate attack on recycled aggregate concrete immersed in sodium sulfate solution for 10 years - Santillan, Lautaro Rodolfo (2020)
The effect of recycled concrete aggregate (RCA) on concrete performance against external sulfate attack (ESA) is not yet fully known. In this paper, recycled aggregate concretes (RAC) with 0, 50, 75 and 100% of RCA contents were evaluated after 10 years of exposure immersed in 50g/l sodium sulfate solution. Sulfate ingress profiles were obtained by wet chemical analyses and FRX. Also, the mineralogy of the ingress profile was evaluated by thermogravimetric analyses. Finally, microcracking development in samples was evaluated by optical fluorescent microscopy image analysis. Although RAC showed a slight increase in sulfate ingress, due to its higher porosity (about 30% higher SO3 content near the surface for 50% or higher replacement ratio than control concrete), a dense new matrix still allows a good performance of RAC to external sulfate attack with even 100% RCA content.